IDENTIFICATION THE CHARACTERISTIC AND LEVEL OF STUDENT’S METACOGNITIVE IN SOLVING REACTION RATE CHEMISTRY PROBLEMS (Universitas Negeri Surabaya, 2018)
The purpose of this study is to identify characteristic and level of student’s metacognitive in solving reaction rate chemistry problems at class XI SMA Negeri 18 Surabaya. In collecting data, the researcher uses document method and interview method, then it would be tested its validity using triangulation method. The results showed that characteristic and level of student’s metacognitive in solving problems each group were different, that is, high ability group had metacognitive characteristic: planning (P-1, P-2, P-3, P-4, P-5), monitoring (M-2, M-3, M-5), and reflection (R-1, R-3) in accordance with appropriate metacognitive level indicator is planning (EP-2, EP-3, FP-1, FP-2), monitoring (EM-2, FM-1), and reflection (FR-1) so the level is reflective use, then the medium ability group has metacognitive characteristic: planning (P-1, P-2, P-3, P-4), monitoring (M-2, M-3), and reflection (R-1) corresponding to appropriate metacognitive level indicators is planning (BP-3, CP-1), monitoring (BM-2, CM-1), and reflection (BR-1) so the level is semi strategic use, then the low ability group has metacognitive characteristic: planning (P-1, P-2, P-3) and monitoring (M-2, M-3) corresponding to the appropriate metacognitive level indicator is planning (BP-2, BP-3), monitoring (BM-1, BM-2), and reflection (AR-1) so the level is aware use. Keywords: Characteristic, Level, Metacognitive